The Relationship of Hypertension and Diabetes Mellitus with Ischemic Stroke - Purnama, Sari Dianita; Panghiyangani, Roselina; Marlinae, Lenie; Husaini, Husaini; Noor, Meitria Syahadatina (Jurnal Berkala Kesehatan, 2024)
Ischemic stroke is a common cause of disabilities among adults around the world and the second reason of death around the world after the first one, ischemic heart disease, the prevalence keeps rising after years. Some of the most common risk factors are hypertension, diabetes mellitus, heart disease, smoking, alcohol consumption, and high blood lipid levels that affect the blood viscosity and the blood clot. This research aims to study some of ischemic stroke’s risk factors which are hypertension and diabetes mellitus. This research is an observational retrospective study with effect size that can be found by secondary using search engines such as Google Scholar, Science Direct, PubMed, etc. The data filtered only for the last 5 years old journal, case-control study, and logistic regression analysis. From the 180 articles, found 14 worth articles about hypertension and diabetes mellitus with stroke ischemic and analyzed using JASP app. The result is hypertension related with ischemic stroke by p-value 0.0003 and mean effect size 4.32 (95% CI 1.97-9.49), then diabetes mellitus also related with ischemic stroke by p-value 0,00001 and mean effect size 2.99 (95% CI 2.28-3.92). Hypertension and diabetes mellitus statistically related with ischemic stroke by meta-analysis.